SISTEM PEMBUKTIAN DALAM PENANGANAN PERKARA PERSELISIHAN HASIL PEMILIHAN UMUM KEPALA DAERAH DAN WAKIL KEPALA DAERAH (PEMILUKADA) DI MAHKAMAH KONSTITUSI - Safi' Safi' (Jurnal Dinamika Hukum, 2011)
The choice of a system of proof in the case handling process within the judiciary is a very important thing. Because the verification system adopted by a judicial institution will determine the quality of the verdict to be taken. Verification system adopted by the Constitutional Court in handling cases disputes the results of the regional head elections as stipulated in Act. No. 24 Th. 2003 had the right to find a material truth which is expected.Key words: verification, constitutional court, material truth